2013
DOI: 10.1016/j.jcp.2012.10.021
|View full text |Cite
|
Sign up to set email alerts
|

A bidirectional coupling procedure applied to multiscale respiratory modeling

Abstract: In this study, we present a novel multiscale computational framework for efficiently linking multiple lower-dimensional models describing the distal lung mechanics to imaging-based 3D computational fluid dynamics (CFD) models of the upper pulmonary airways in order to incorporate physiologically appropriate outlet boundary conditions. The framework is an extension of the Modified Newton’s Method with nonlinear Krylov accelerator developed by Carlson and Miller [1, 2, 3]. Our extensions include the retention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Another avenue that is receiving recent interest is the integration of distal lung mechanics through coupling of the 3D CFD model with 1D or 0D models at each outlet. (80,84,85) This should allow for a more realistic definition of airflow distribution at model outlets. DeBacker et al (86) showed good agreement between CFD predictions of airflow distribution and those derived from SPECT/CT by accounting for airway resistance.…”
Section: Fig 2 Coronal Slices Of 3d Single Photon Emissionmentioning
confidence: 99%
“…Another avenue that is receiving recent interest is the integration of distal lung mechanics through coupling of the 3D CFD model with 1D or 0D models at each outlet. (80,84,85) This should allow for a more realistic definition of airflow distribution at model outlets. DeBacker et al (86) showed good agreement between CFD predictions of airflow distribution and those derived from SPECT/CT by accounting for airway resistance.…”
Section: Fig 2 Coronal Slices Of 3d Single Photon Emissionmentioning
confidence: 99%
“…24 However, not until recently have these methods been applied to the respiratory system. 3,27,28,30 Typically, a multi-scale numerical model includes a 3D CFD description of the large airways and a 1D 30 or 0D 3,28 lower-dimensional model representing the smaller airways and peripheral tissue. These models enable more realistic 3D unsteady flow simulations because they do not require direct description of time-dependent flow and pressure waveforms at the distal branches, which are typically unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Employing impedance boundary conditions in a ventilated healthy human 3D lung CFD model, Comerford et al 14 demonstrated that downstream impedance significantly influences the overall pressure field, but has little effect on the flow velocity. Additionally, while several groups 3,27,28,30 have made significant advances in multi-scale respiratory modeling, none of these works directly parameterized their lower dimensional models from animal or patient in-vivo specific data. In addition, the recent work of Wongviriyawong et al 53 showed that their lumped parameter model of the human lung could only reproduce the ventilation measurements if it included the downstream resistances and compliances tuned from healthy and asthmatic measurements.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been used extensively in different fields. This technique was applied successfully in environmental engineering, mechanical engineering, and bio engineering [9,29,39,50]. The advantage of proposed method is the reduction in the overall computation time.…”
Section: Introductionmentioning
confidence: 99%